The nature of language in the legal field : Kurdish language as an example - Shadan Shukr Sabr; Rozhan Noori Abdulla (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The current research focuses on forensic linguistics with a particular focus on forensic linguistics in the Kurdish language. Forensic linguistics has its own features and terms different from those used in daily or academic discourses, which are discussed in this research. The current also attempts to study the degree to which lawmakers pay attention to the language when drafting a law because understanding the law is subjected to understanding the language used in writing the law. The research found that the language of the law is measurable, detailed, and specific. The research also found that in order for a law to be enforced and followed, lawmakers, or anyone who is dealing with laws, need to follow the rules of language and be familiar with the rules of language. The research also shows because language is governing the laws, the rules of language, especially forensic linguistics must be clarified and followed.